Higher dietary live microbe intake is linked to reduced risk of metabolic syndrome and mortality: a cross-sectional and longitudinal study - Huang, Shan; Xiao, Haixia; Xiao, Huanshun; Liu, Lu; Cai, Shuangming (Frontiers in Nutrition, 2025)
BackgroundThe association between dietary live microbe intake and metabolic syndrome (MetS) prevalence, as well as its impact on all-cause and cardiovascular disease (CVD) mortality in MetS patients, remains underexplored.MethodsA total of 38,462 individuals from the National Health and Nutrition Examination Survey (NHANES) 1999–2018 were analyzed. Based on the live microbial level of the consumed foods, participants were divided into three dietary live microbe intake groups: low, medium, and high. Foods with medium and high live microbe content were aggregated into a medium-high consumption category. MetS was defined based on NCEP-ATP III criteria. Survey-weighted logistic regression assessed the cross-sectional association with MetS prevalence, while Cox proportional hazards models evaluated mortality risks in 12,432 individuals with MetS, among whom 2,641 all-cause and 901 CVD deaths occurred.ResultsHigher dietary live microbe intake was significantly associated with lower odds of MetS. Compared to the low intake group, participants in the high intake group had a 12% lower risk of MetS in the fully adjusted model (OR: 0.88; 95% CI: 0.80–0.97; p = 0.01). Among MetS components, significant inverse associations were observed for low HDL-C, elevated TG, and elevated BP. Participants with high dietary live microbe intake demonstrated a significantly lower risk of all-cause mortality (HR: 0.85; 95% CI: 0.77–0.94; p = 0.002) and CVD-specific mortality (HR: 0.71; 95% CI: 0.55–0.92; p = 0.001) compared to the low intake group. Kaplan–Meier survival curves revealed better survival probabilities in individuals with medium and high intake levels, with significant differences across groups (log-rank p < 0.005). Quantitatively, each 100g increase in MedHi foods was associated with 6% lower all-cause mortality (HR: 0.94; 95% CI: 0.90–0.99; p = 0.01) and 8% lower CVD mortality (HR: 0.92; 95% CI: 0.84–1.00; p = 0.05).ConclusionDietary live microbe intake is inversely associated with the prevalence of MetS and its key components, particularly low HDL-C, elevated TG, and elevated BP. In individuals with MetS, higher live microbe intake is associated with reduced all-cause and CVD-specific mortality. These findings suggest that dietary live microbes are a promising modifiable factor for MetS prevention and management, as well as for improving long-term survival outcomes.